Government co-option of civil society: exploring the AKP's role within Turkish women's CSOs. Issue 3 (3rd April 2018) - Doyle, Jessica Leigh
ABSTRACT: Mainstream academic and policy literature emphasizes the nexus between an active and vibrant civil society sector and greater political accountability. As a result, support for civil society has become central to international policy efforts to strengthen democracy in the Middle East North Africa (MENA) region. However, the empirical evidence presented in this article questions the validity of this assumption. Drawing on information gathered through 38 in-depth qualitative interviews with women's organizations from across the seven administrative regions of Turkey, and key representatives from the ruling Justice and Development Party (AKP), this article analyses the role of the AKP government in co-opting and influencing women's organizations in Turkey. The results that emerge demonstrate that the government is actively involved in fashioning a civil society sector that advances their interests and consolidates their power. Independent women's organizations report that they are becoming increasingly excluded from policy and legislative discussions, as seemingly civic organizations are supported and often created by the government to replace them. These organizations function to disseminate government ideas in society and to provide a cloak of democratic legitimacy to policy decisions. These findings and their implications have significant consequences for theory and policy on civil society and its role in supporting democracy.